Apical Root Resorption: A Prospective Radiographic Study of Maxillary Incisors - Kocadereli, Ilken; Yesil, Turkan Nadire; Veske, Pınar Sahin; Uysal, Serdar (European Journal of Dentistry, 2011)
Objectives: The aim of this study was to determine the prevalence of apical root resorption in maxillary incisors during the initial stages of active orthodontic treatment and to test the hypothesis that root resorption increases with the progress of the treatment. Methods: The study sample consisted of 80 teeth of 20 patients (14 female, 6 male) with a mean age of 14.9±2.8 years. Root resorption was determined with standardized digitized periapical radiographs. All the periapical radiographs were obtained at the beginning of orthodontic treatment (T0) and 3 months (T1), 6 months (T2) and 9 months (T3) after the beginning of the treatment by a paralleling device. They were digitalized as 600 dpi with a flatbed scanner and analyzed by software for image analysis at 400x magnification utilizing a personal computer. Results: All of the 4 maxillary incisors had an increasing amount of resorption during the 9-month period. The amount of root resorption between the time intervals was statistically significant (P<.05). Conclusions: Root resorption of maxillary incisors can be detected in the early stages of orthodontic treatment and appears to be related to treatment duration. According to 9-month evaluation period, apical root resorption is of limited clinical significance for the average orthodontic patient. (Eur J Dent 2011;5:318-323)
Keywords: Orthodontics; Root resorption; Maxillary incisors; Prevalence